If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2t-(t-1)-1-2=3t(2-1t)+4
We move all terms to the left:
2t-(t-1)-1-2-(3t(2-1t)+4)=0
We add all the numbers together, and all the variables
2t-(t-1)-(3t(-1t+2)+4)-1-2=0
We add all the numbers together, and all the variables
2t-(t-1)-(3t(-1t+2)+4)-3=0
We get rid of parentheses
2t-t-(3t(-1t+2)+4)+1-3=0
We calculate terms in parentheses: -(3t(-1t+2)+4), so:We add all the numbers together, and all the variables
3t(-1t+2)+4
We multiply parentheses
-3t^2+6t+4
Back to the equation:
-(-3t^2+6t+4)
-(-3t^2+6t+4)+t-2=0
We get rid of parentheses
3t^2-6t+t-4-2=0
We add all the numbers together, and all the variables
3t^2-5t-6=0
a = 3; b = -5; c = -6;
Δ = b2-4ac
Δ = -52-4·3·(-6)
Δ = 97
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-\sqrt{97}}{2*3}=\frac{5-\sqrt{97}}{6} $$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+\sqrt{97}}{2*3}=\frac{5+\sqrt{97}}{6} $
| (4/5y)(15/2)(30y/6)=10 | | 5x=34+2x | | 2k÷5=7 | | 5m-9m=-16-12 | | 3(2x-3)=(3x+8) | | X-3/3=2x+1/7 | | (4x+5)÷2x=39÷12 | | x+8+15=-4 | | 6x-x=4-4 | | a-30=3 | | (x–2)(x–5)=18 | | 3.8x–7=8.2 | | ?-6x5=10 | | x+(x*0.20)=1920 | | (9/7x)(14/3)(18x/6)=3 | | y2-15y-16=0 | | (x+(x*0.20))-1043=1920 | | x+(x*0.20)-1043=1920 | | 0.062=6.2×10n | | 3x-6(3-4x)=9x2 | | -3(-3x-3)+3=66 | | 5x^2-51x+5=0 | | -66=3(5b-2) | | 5x+x+23=3x+34 | | 4,8/15,36=x/8 | | -z+1=1-z | | 64x^2+64x+16=0 | | 64x2+64x+16=0 | | x=0.02x^2+0.05x+0.04 | | 18=3y= | | 81z^2-4=0 | | 18-(3a-12)=8a |